STRATEGI KOMUNIKASI PEMASARAN DESA WISATA DI KABUPATEN PANDEGLANG (STUDI PADA BIDANG PEMASARAN DESA WISATA CURUG RAHONG DI KABUPATEN PANDEGLANG BANTEN) - Alfonsius Hasiholan, (2020)
This research was made based on the background of the increasing needs of the people of Indonesia for tourism activities that are increasingly large, the increase will lead to a domino effect. The purpose of this study was to find out how the marketing communication strategy undertaken by the curug rahong tourism village manager to increase tourist visits. The research method used is a qualitative type with descriptive study analysis. Data collection through in-depth interviews, observation, and documentation. The main concept used is marketing communication strategy. The results of this study indicate that the manager of the curug rahong tourism village carries out a marketing communication strategy by prioritizing the interactive / internet marketing mix, personal selling, sales promotion, and public relations. In planning the marketing communication strategy the manager of Curug Rahong Tourism Village applies a plan based on distinctive competence. The researcher also concluded that the manager of the Rahong Curug tourism village had carried out an effective and efficient communication strategy activity, the manager of the Curug Rahong tourism village had carried out an internal analysis of the selection of the communication strategy used, creating a close relationship with the client. continously. For the development of marketing communication strategies. Keywords: Strategy Marketing Communication, Event, Marketing Communication Mix